L’Évolution de socle précambrien dans la région de Qagssimiut, Groenland méridional. - Ayrton, S. N.; Burri, M. (Meddelelser om Grønland, 1967)
The rocks of the Qagssimiut area, South Greenland, belong, apart from a few late dolerite dykes, to the Precambrian shield. Their history was found to be very complex. An orogenic period affected formations mainly composed of quartzites and amphibolitic schists which now occupy but a very small percentage of the area. These rocks, having been submitted to at least two periods of deformation (during which a set of folds with a NW-SE trend, and a major, younger NE-SW set were developed), were subsequently intruded by massifs and plugs of ultrabasic material, which are very much more widely preserved. Widespread granitisation then occurred; in particular, the pre-existent rocks were (partly) transformed into granite, which is by far the principal component of the Qagssimiut area. The processes apparently took place in tranquil conditions. Basic intrusion also takes the form of sheets and dykes, concentrated mainly in the southern parts of the area. Some of these sheets are conspicuously veined and replaced by granite or aplite. The striking characteristics of this phenomenon, which involves static replacement and progressive consumption of basic material by acid, are described in some detail. The contrast between basic and acid material is remarkable, as is the alternation of phases of basic intrusion and granitisation, which occurred under conspicuously stable conditions. The emplacement of small massifs of homogeneous, pink or white microgranite preceded the Gardar period, characterised by the intrusion of dykes (lamprophyres, dolerites, trachytes, porphyries) and block-faulting. A long hiatus separated the end of the Gardar period from the next event, the (Tertiary?) intrusion of two generations of dolerite dykes. They are fresh and never faulted. Quaternary phenomena are mainly related to the activity of the ice-cap, whose traces are ubiquitous.